Placement tutors’ perceptions about University traineeship: a central point of view for a circular and integrated model - Renda, Eleonora; Salerni, Anna; Malerba, Dania (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
This paper aims to reflect on the intership model in first and second level degree courses in “Education and Training” at Sapienza University of Rome, exploring the viewpoint of tutors who follow students during their training. The circular and integrated model allows to plan an appropriate training to achieve studying and working aims, considering students’ skills, knowledge and interests, taking into account also the labour market development. Data were collected through a semi-structured questionnaire administered at the end of the training experience and completed by 144 tutors. The results coming from the analysis are discussed underlining strengths and weaknesses of the internship program.